A comparison of the frequency of familial suicide attempts across eating disorder diagnoses. Issue 6 (15th February 2017) - Pisetsky, Emily M.; Peterson, Carol B.; Mitchell, James E.; Wonderlich, Stephen A.; Crosby, Ross D.; Le Grange, Daniel; Hill, Laura; Powers, Pauline; Crow, Scott J.
Abstract: This study examined the prevalence of reported suicide attempts among family members of individuals with an eating disorder (ED). 1870 individuals presenting for ED treatment reported whether their family members ever made a suicide attempt using the Eating Disorders Questionnaire. A lifetime suicide attempt by any family member was reported by 10.8% ( n = 202) of the sample and ranged from 7.0% of those with eating disorder not otherwise specified to 16.1% of those with purging disorder. Controlling for age and gender, individuals with bulimia nervosa had a higher prevalence of any familial suicide attempt and mother suicide attempt than individuals with EDNOS; no other differences were observed across ED diagnoses. There were no differences in prevalence of reported suicide attempts made by fathers, brothers, sisters, uncles, or aunts by ED diagnosis. Findings support a growing literature indicating a familial association between EDs and suicide risk.